Fibrillar Aβ causes profound microglial metabolic perturbations in a novel APP knock‐in mouse model. (1st February 2022) - Xia, Dan; Lianoglou, Steve; Sandmann, Thomas; Calvert, Meredith; Suh, Jung; Thomsen, Elliot; Dugas, Jason; Pizzo, Michelle E.; DeVos, Sarah L.; Earr, Timothy K.; Lin, Chia‐Ching; Davis, Sonnet; et al.
Abstract: Background: Microglial dysfunction is believed to play a pathogenic role in Alzheimer's disease (AD). Microglia respond to various pathogenic drivers of AD, including amyloid‐ß (Aß) and tau, but the mechanisms by which microglia may become dysfunctional and contribute to disease remain unclear. Here, we aim to characterize the amyloid‐ß related pathology and microglial responses in an engineered APP knock‐in mouse model of familial AD ( App SAA ). Method: To circumvent the numerous limitations inherent to transgenesis, we used a knock‐in strategy to humanize the Aß sequence of the murine App gene and introduced three FAD mutations ‐ Swedish (KM670/671NL), Arctic (E693G) and Austrian (T712I) ‐ using homologous recombination. We then conducted an extensive biochemical and histological characterization of various tissues from the three resulting genotypes at various ages. Finally, we conducted a deep‐phenotyping analysis of brain‐sorted microglia using multi‐omics approaches. Result: The App SAA knock‐in mouse model recapitulates key pathological features of AD such as a progressive accumulation of parenchymal amyloid plaques and vascular amyloid deposits, altered glial responses and increased levels of markers of neurodegeneration such as CSF Tau and neurofilament light chain. We found lipid accumulation and an exacerbated disease‐associated transcriptomic response in methoxy‐X04‐positive, phagocytic microglia. Conclusion: Altogether, our in‐depth analysis of the App SAA knock‐in mouse model confirms emergence of disease‐relevant biology and progressive accumulation of pathological hallmarks of AD. Our data lends further support to the notion that phagocytic microglia undergo profound cellular alterations, including lysosomal dysfunction, lipid dyshomeostasis, and other metabolic changes. Since this new mouse model can be used to investigate multiple relevant aspects of AD biology, we have made it broadly available to the scientific community.